Performance Analysis Of Mono-bit Digital Instantaneous Frequency Measurement (Difm) Device - Y. Norouzi; H. Shahbazi; S. Mirzaei (AUT Journal of Electrical Engineering)
Instantaneous Frequency Measurement (IFM) devices are the essential parts of anyESM, ELINT, and RWR receiver. Analog IFMs have been used for several decades. However, thesedevices are bulky, complex and expensive. Nowadays, there is a great interest in developing a wideband, high dynamic range, and accurate Digital IFMs. One Digital IFM that has suitably reached allthese requirements is mono-bit zero-crossing IFM, made by some different producers at present. Inthis paper, the performance of mono-bit digital Instantaneous Frequency Measurement (IFM) deviceis analyzed. This analysis includes quantization error, thermal noise, clock jitter, comparator bias andalso “Pulse-on-Pulse” occurrence. The error limits due to all these factors are computed and analyzed,and a unified approach to the system design is presentedIn this paper, the performance of mono-bit digital Instantaneous frequency measurement (IFM) device is analyzed. This analysis includes quantization error, additive (thermal) noise, clock jitter, comparator bias and also “Pulse-on-Pulse” occurrence. The error limits due to all these factors are computed and analyzed, and a unified approach to the system design is presented